What is the student's level? Analyzing Students' English Proficiency Levels in High Education Level - Rais, Burhanudin; Awwalia , Luthfi (STAIN Sultan Abdurrahman Kepulauan Riau, 2025)
English has become an essential language for many purposes, including educational needs. However, English learning still has various obstacles, such as the lack of adequate environment and facilities for learning English, including Sintang, a border area. The environment and facilities greatly influence students' English learning. It raises the question of how good the English skills are there. However, the researchers' concern in this study is students at the university level. Universities were chosen as relevant subjects because they are at the highest level of English learning in formal schools. To achieve this goal, researchers use qualitative methods and conduct English language proficiency tests guided by CEFR on students in Sintang. There were 149 results obtained by researchers after conducting the test, but only 139 can be taken as data for this study. This study's results indicate that most students are basic users.